The influence of die geometry and workpiece mechanical properties in T-Shape friction test - Taureza, Muhammad (2014)
In this study, T-Shape friction test was redesigned to make it more suitable for application to microforming processes. Workpiece with aspect ratio (length/diameter) of 5 was proposed in order to ease workpiece handling. The die geometry was also modified from the original test to improve friction sensitivity especially within the range of friction factors commonly observed in metal forming. Geometric deviation of the die was simulated using Deform-2D to establish the acceptable tolerance for the fabrication. The effect of variation in workpiece mechanical properties on the test behavior was also investigated through Deform-2D simulation. Based on simulations on a 1 mm diameter copper workpiece, a tolerance of 0.01 mm (1% of workpiece diameter) was found to be the most suitable for the die fabrication. In addition, it was shown that variations in workpiece mechanical properties of up to 10% do not significantly influence the friction test results. Ultimately, T-Shape test experiment was conducted using copper workpieces to examine how the test complied with the friction behavior observed in the experiment.